2020
DOI: 10.1155/2020/9818652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neuroligin1 and Neurexin1 on the Colonic Motility in a Mouse Model of Neuronal Intestinal Dysplasia

Abstract: Aim. To investigate the expressions of neuroligin1 (NL1) and neurexin1 (NX1) in a mouse model of neuronal intestinal dysplasia (Tlx2-/- mice) and to explore their effects on colonic motility. Methods. Immunohistochemistry staining was employed to explore the histological appearances of NL1, NX1, the presynaptic marker of glutamatergic synapses VGLUT1, and the subunit of NMDA receptors of NR1 in the colon of mice with or without Tlx2 mutation. Western blotting and qRT-PCR were performed to detect their relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Tlx2 −/− mice, a verified model of IND, usually show hyperplasia of the intestinal ganglion and persistence of immature enteric neurons after birth (18,27). In our previous studies, Tlx2 −/− mice showed obvious abdominal distension and impaired colonic motility, and 26% (33/127) of the mice died 8 weeks after birth (25), which may be related to histopathological changes in the colonic tissues of Tlx2 −/− mice.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Tlx2 −/− mice, a verified model of IND, usually show hyperplasia of the intestinal ganglion and persistence of immature enteric neurons after birth (18,27). In our previous studies, Tlx2 −/− mice showed obvious abdominal distension and impaired colonic motility, and 26% (33/127) of the mice died 8 weeks after birth (25), which may be related to histopathological changes in the colonic tissues of Tlx2 −/− mice.…”
Section: Discussionmentioning
confidence: 91%
“…The pathogenesis of IND is unresolved; however, several mechanisms have been proposed, including secondary infections, inflammation, and developmental failures (22)(23)(24). It has been confirmed that the seriously impaired colonic motility of IND is related to abnormal innervation between ENS and intestinal smooth muscle cells (25,26). Tlx2 −/− mice, a verified model of IND, usually show hyperplasia of the intestinal ganglion and persistence of immature enteric neurons after birth (18,27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the etiopathogenesis of IND-B is widely debated. It is mainly recognized as genetic alterations resulting in intestinal neuronal system development disorder ( 6 , 7 ). However, IND-B can also be understood as a secondary phenomenon due to congenital intestinal obstructions or local inflammatory processes ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the mice were fully awake (the standard was that the mice could turn over freely and climb up), the study began by observing the time to bead ejection. These methodologies were performed and modified as previously described [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%